2008
DOI: 10.1007/s11517-008-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface EMG and acceleration signals in Parkinson’s disease: feature extraction and cluster analysis

Abstract: We present an advanced method for feature extraction and cluster analysis of surface electromyograms (EMG) and acceleration signals in Parkinson's disease (PD). In the method, 12 different EMG and acceleration signal features are extracted and used to form high-dimensional feature vectors. The dimensionality of these vectors is then reduced by using the principal component approach. Finally, the cluster analysis of feature vectors is performed in a low-dimensional eigenspace. The method was tested with EMG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 19 publications
(35 reference statements)
2
73
0
1
Order By: Relevance
“…The power spectral densities of EMG and ACC and their cross-spectral density were estimated here by using Welch's averaged periodogram method. The coherence parameter is the area of the magnitude squared coherence spectrum in the frequency range [0-50] Hz (Rissanen et al, 2008). …”
Section: Emg Featuresmentioning
confidence: 99%
“…The power spectral densities of EMG and ACC and their cross-spectral density were estimated here by using Welch's averaged periodogram method. The coherence parameter is the area of the magnitude squared coherence spectrum in the frequency range [0-50] Hz (Rissanen et al, 2008). …”
Section: Emg Featuresmentioning
confidence: 99%
“…Accelerometers have been applied outside the operating room (OR) for a wide variety of purposes, e.g., to characterize pathological tremor [8,13], to compare it with physiological tremor [20,35,36], and to evaluate the severity and evolution of tremor [28,29,40] and the tremor-alleviating effect of drugs or DBS [22,36,47]. Pulliam et al [34] used motion sensors during postoperative DBS pulse generator programming to develop automated programming algorithms and concluded that objective assessment can improve patients' outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because this electrode is very thin and can bend freely, it does not leave marks on the skin during prolonged ECG measurements. This property of the electrode allows the subject to feel comfortable throughout the measurement and also allows for make good contact with the subject's skin when used in bioimpedance measurement, facial movement detection, or EMG measurement [5,11,13,16].…”
Section: Discussionmentioning
confidence: 99%